Perfil de marcadores de angiogênese nas gestantes com pré-eclâmpsia e a correlação com os níveis da pressão arterial média - Patricia Goncalves Teixeira (2006)
Objective: the pathophysiological clinical findings of preeclampsia (hypertension and proteinuria) seem to be associated with inadequate responses to and/or production of angiogenic factors. This study was performed to evaluate plasmatic levels of vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) in pregnant women with or without preeclampsia and whether any alteration in systemic levels of these angiogenic markers would be associated with increasedmean arterial pressure. Study Design: twenty-three preeclamptic and nine normotensive pregnant women from the Maternity of Hospital das Clínicas in Belo Horizonte were assessed by NHBPEPWG 2000 criteria and blood samples were collected at the time of diagnosis (33-35 weeks). The plasmatic levels of VEGF and PlGF were determined by ELISA assay and mean arterial pressure was calculated (MAP= 2/3 diastolic arterial pressure + 1/3 sytolic). Correlation between MAPvalues and angiogenic markers concentration was determined through regression analysis. Results: VEGF concentration (243.3±193 pg/ml) inpreeclamptic woman were not statistically different from the levels (160.6±143 pg/ml) of non preeclamptic pregnant. However, plasma concentration of PlGF was lower in preeclamptic versus normotensive pregnancies (40.8±37.5 versus 480±374 pg/ml). Inverse correlation was observed between PlGF plasma levels and mean arterial pressure. A decrease in 1pg/ml of PlGF resulted in 6.58 mm Hg increase in MAP (p=0.002). Conclusion: these results support a determinant role of PlGF in mean arterial pressure in pregnant women.